Risk Factors for Mortality in Anti-NMDAR, Anti-LGI1, and Anti-GABABR Encephalitis - Zhong, Rui; Chen, Qingling; Zhang, Xinyue; Zhang, Hanyu; Lin, Weihong (Frontiers in Immunology, 2022)
Abstract Objective: We aimed to investigate the mortality rate and identify the predictors of death in patients with anti-NMDAR, anti-LGI1, and anti-GABABR encephalitis. Methods: Patients with anti-NMDAR, anti-LGI1, and anti-GABABR encephalitis were recruited from the Neurology Department of the First Hospital of Jilin University from March 2015 to November 2021. The primary outcome variable was a binary variable of death vs. survival. The potential risk factors for mortality were evaluated. The mortality rates were determined, and the independent predictors of death were identified using multivariable logistic regression analysis. Results: A total of 100 hospitalized patients with anti-NMDAR, anti-LGI1, or anti-GABABR encephalitis were included in the final analysis. Fifteen patients (15%) died during a median follow-up period of 18 months. The mortality rates were 10% for anti-NMDAR encephalitis, 2.8% for anti-LGI1 encephalitis and 41.7% for anti-GABABR encephalitis. The multivariable analysis results showed that older age at onset (adjusted odds ratio (OR) = 1.017, 95% confidence interval (CI)=1.009-1.136; P=0.023) was independently associated with an increased risk of death. Antibody type was also associated with mortality. Patients with anti-GABABR encephalitis had 13.458-fold greater odds of dying than patients with anti-LGI1 encephalitis (adjusted OR = 13.458, 95% CI=1.270-142.631; P=0.031). Conclusion: The general mortality rate of anti-NMDAR, anti-LGI1, and anti-GABABR encephalitis was 15%. Age at onset and type of autoimmune encephalitis antibody were independent predictors of death in these patients.